The Use of Information and Communication Technology in the Training for Ethical Competence in Business - Kavathatzopoulos, Iordanis (Journal of business ethics, 2003)
Information and communication technology has certain advantages that can contribute positively in business ethics education programmes. It is necessary, however, to identify first the factors critical for acquiring ethical competence and later to proceed to the construction and use of such tools, in order to ensure that these tools are indeed adapted to the process and the goals of business ethics education. Based on psychological theory and research, it is argued that one such crucial factor is the psychological construct of ethical autonomy. The strengths and weaknesses of information and communication technology tools are discussed in accordance with this, and some suggestions are given on fruitful ways to incorporate these tools in business ethics education.